Comprehensive Genomic Characterization of Long Non-coding RNAs across Human Cancers - Yan, Xiaohui; Hu, Zhongyi; Feng, Yi; Hu, Xiaowen; Yuan, Jiao; Zhao, Sihai D.; Zhang, Youyou; Yang, Lu; Shan, Weiwei; He, Qun; Fan, Lingling; Kandalaft, Lana E.; et al. (Cancer cell, 2015)
The discovery of long non-coding RNA (lncRNA) has dramatically altered our understanding of cancer. Here, we describe a comprehensive analysis of lncRNA alterations at transcriptional, genomic, and epigenetic levels in 5,037 human tumor specimens across 13 cancer types from The Cancer Genome Atlas. Our results suggest that the expression and dysregulation of lncRNAs are highly cancer type specific compared with protein-coding genes. Using the integrative data generated by this analysis, we present a clinically guided small interfering RNA screening strategy and a co-expression analysis approach to identify cancer driver lncRNAs and predict their functions. This provides a resource for investigating lncRNAs in cancer and lays the groundwork for the development of new diagnostics and treatments. [Display omitted] •lncRNA dysregulation was characterized in 5,037 tumor samples across 13 cancer types•lncRNAs are altered in cancers at transcriptional, genomic, and epigenetic levels•The expression and dysregulation of lncRNAs are strikingly cancer-type specific•This study provides a resource to systematically identify cancer driver lncRNAs Yan et al. analyze long non-coding RNA (lncRNA) alterations at transcriptional, genomic, and epigenetic levels across multiple cancer types from TCGA datasets and cancer cell lines. They also present a screening strategy and “co-expression” approach using the integrative data to identify cancer driver lncRNAs.